Drug use patterns among Thai illicit drug injectors amidst increased police presence - Suwannawong Paisan; Kaplan Karyn; Fairbairn Nadia; Hayashi Kanna; Werb Dan; Lai Calvin; Kerr Thomas (BMC, 2009)
Abstract Thailand has traditionally pursued an aggressive enforcement-based anti-illicit drug policy in an effort to make the country "drug-free." In light of this ongoing approach, we sought to assess impacts of enforcement on drug use behaviors among a cohort of injection drug users (IDU) in Thailand. We examined drug use patterns among IDU participating in a cross-sectional study conducted in Bangkok (n = 252). Participants were asked to provide data regarding patterns of drug use in the previous six months, including types of drugs consumed, method of consumption, frequency of use, and weekly income spent on drugs. We also conducted bivariate analyses to identify a possible effect of a reported increase in police presence on measures of drug use and related risk behaviors among study participants. One hundred fifty-five (61.5%) individuals reported injection heroin use and 132 (52.4%) individuals reported injection midazolam use at least daily in the past six months. Additionally, 86 (34.1%) individuals reported at least daily injection Yaba and Ice (i.e., methamphetamine) use. Participants in our study reported high levels of illicit drug use, including the injection of both illicit and licit drugs. In bivariate analyses, no association between increased police presence and drug use behaviors was observed. These findings demonstrate high ongoing rates of drug injecting in Thailand despite reports of increased levels of strict enforcement and enforcement-related violence, and raise questions regarding the merits of this approach.